Knowledge of COVID-19 and the psychological status of parents: a retrospective survey in Wuhan, Hubei - Lei Wang; Jing Cheng; Lin Lv; Yaqi Xu; Yutong Zhang; Honghui Gan; Change Xiong; Guiping Wang; Can Mei; Linwanyue Chen; Lu He; Shuliu Pan; et al. (BMJ Open)
Objective During the COVID-19 pandemic, many parents faced heightened stress, anxiety and depression due to the local and global COVID-19 mitigation measures and lockdowns.Design This is a cross-sectional study.Setting This study used stratified whole-cluster sampling to randomly select three elementary schools within Ezhou City.Participants An online survey was administered to the parents of students in one or two classes in grades 1–6, respectively, of each school. Among them, males account for 30.4% and females account for 69.6%. The inclusion criteria included (1) the parent or legal guardian of a primary school student or a person directly responsible for the child’s education and (2) the ability to operate a computer or smartphone to complete the survey. Only one representative from each family was allowed to participate, and surveys with incomplete data were considered invalid and thus excluded.Results A total of 764 participants completed the online survey. Overall, 90.4% of the participants were concerned about their children’s mental health and learning during the pandemic. Additionally, 97.0% were aware of the typical symptoms of COVID-19. Only 48.0% of the participants felt the pandemic negatively impacted their lives. The average psychological status score among parents was 87.79±8.91, with 51.6% showing signs of high psychological distress. Significant differences in psychological status were linked to age, education, professional background, sleep status, personal views on the pandemic’s impact and concern for children’s learning (p<0.05). Multiple logistic regression analysis revealed that a negative perception of the pandemic’s impact on one’s life (OR 0.367, 95% CI: 0.272 to 0.493) was associated with psychological distress.Conclusion Parents of school children in Ezhou City have a good knowledge base on COVID-19 infection and have a high awareness of the corresponding protective measures. However, priority attention and care should be given to individuals who have experienced mental distress in relation to the pandemic.